A survey on indoor patient satisfaction in a private tertiary level surgical hospital in central India - Bhole, Shantala S.; Bhole, Sagarika S.; Bhole, Sadashiv D.; Upadhye, Jayshree J. (International Journal of Research in Medical Sciences, 2017)
Background: Patient satisfaction is an extremely important factor responsible for the success and growth of any hospital. Hence this survey was done in a super-speciality Uro-gynaecology hospital in Nagpur, Central India to assess the patient satisfaction for indoor facilities. Methods: The present study was conducted over a period of 4 months in 100 indoor patients. These patients were asked to fill up a questionnaire just before they were discharged. Results: 88% respondents found the service by reception staff as excellent. 64% were admitted and allotted rooms within 30 minutes of arrival. 94% said that the time given by doctors was satisfactory. 96% were extremely satisfied with the disease description, 98% said that the perception of efficiency of doctors and the details of investigations discussed were excellent. 90% felt that the number of visits by doctors were adequate. Availability of medicines in the pharmacy was there for most of the times (98%). Drinking water and availability of toilets, electricity and cleanliness was present (94%). 52% were really satisfied with the final bill. Conclusions: Patients are satisfied regarding the basic amenities of the hospital and the provision for water and cleanliness levels. They are happy with the attitude and communication skills of the doctors, they expressed satisfaction about the availability of in-house pharmacy too.